Recurrent angina from chronic coronary obstruction following transcatheter aortic valve implantation - Mohamad Kabach; Abdulah Alrifai; Stefanie Furlan; Fares Alahdab (Avicenna Journal of Medicine, 2016)
Severe aortic stenosis and coronary artery disease often coexist. Coronary angiography (CA) and percutaneous coronary intervention (PCI) can be challenging in patients with prior transcatheter aortic valve implantation (TAVI). Depending on the type and position of the implanted valve, the procedure can be challenging or even unfeasible due to interference of diagnostic catheters and valve parts. The correct positioning of the TAVI prosthesis during TAVI was identified as an important factor with regard to the feasibility of subsequent CA or PCI. TAVI has been also associated with vascular, cerebrovascular and conduction complication. One is rare but life-threatening complication, coronary ostial obstruction. Coronary ostial obstruction can develop, especially if a safety check of more than 10 mm of coronary ostial height is not taken into consideration during TAVI. This complication can cause recurrent episodes of angina and can severely worsen the patient′s cardiac systolic function.